Hubungan Kepuasan Pasien dengan Waktu Tunggu Pasien Rawat Jalan Rumah Sakit X - Tata Arayan; Lilik Sriwiyati; Tunjung Sri Yulianti; I Putu Juni Andika (CV Edujavare Publishing, 2025)
Patient satisfaction is an important indicator of healthcare service quality, one of which is influenced by waiting time. Initial observation showed that the waiting time in the general polyclinic was still long, around 90–120 minutes. This study aims to determine whether there is a relationship between waiting time and patient satisfaction in outpatient installations. We conducted an observational study with a cross-sectional design. The population was 100 outpatients at Dr. Oen Hospital, Solo Baru, who visited in 2024. Using a purposive sampling technique, a sample of 64 patients was taken. There were two main variables studied, namely waiting time (measured by an observation sheet) and patient satisfaction (measured by a questionnaire). Data were analyzed using chi-square test. Most patients (79.7%) waited > 60 minutes with an average of 74.98 minutes, but 71.9% were still very satisfied. The chi-square analysis showed no significant relationship between waiting time and patient satisfaction (p = 0.399). Based on the results of the study, it can be concluded that the length of waiting time for registration does not affect patient satisfaction in outpatient installations. However, it is still recommended that the hospital continue to strive to reduce patient waiting time so that service capacity increases.